Métodos de manutenção de umidade do solo no cultivo do girassol e cártamo em condições controladas - Fontenelli, Julyane Vieira (2014)
The water content of the soil is one of the most important factors limiting the growth and development of plants. Thus, the uniformity of soil moisture, in agricultural experimentation, is essential for reduce variability within treatments, reducing the experimental errors arising from the management of irrigation. The objective was to evaluate methods of maintaining soil moisture, using as indicator plants sunflower (Helianthus annuus L.) and safflower (Carthamus tinctorius L.), grown under controlled conditions. Was performed experiments simultaneously, one sunflower cultivating and another safflower, in the period between the months from August to October 2014, in a greenhouse of the Federal University of Mato Grosso, using an Oxisol. The experimental treatments consisted of the four methods of maintaining soil moisture (tensiometer, Irrigas, gravimetric method and autoirrigante system) in eight replicates. The variables analyzed were: number of leaves, plant height, relative chlorophyll index, stem diameter, stomatal conductance, diameter and number of chapters, number of branches, dry mass of the chapters, leaves, stem, root, aerial part and total. The water consumption and water use efficiency for dry mass of chapters, were also evaluated for both cultures. The development and production of indicator plants, sunflower and safflower were influenced by the methods of soil moisture maintenance in cultivation under controlled conditions. The autoirrigante system is technically indicated for making water management during the vegetative growth period of indicator plants. The larger blades were applied when employed the gravimetric method. The lowest values of morphological and productive parameters were found when the maintenance of soil moisture was performed with the Irrigas sensor. The management of irrigation of sunflower and safflower based on the gravimetric method is sufficient to provide the highest accumulation in shoot and root and consequently increase in water consumption of crops.